Peningkatan Kapasitas Ibu Dalam Upaya Meningkatkan Keragaman Makanan Balita Melalui Edukasi - Putri, Pratiwi Hariyani; Wulandari, Catur; Mutiarani , Anugrah Linda; Dwijayanti , Ira; Susantri, Merry (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The problem of nutrition in toddlers is still a global challenge and is the goal of SDG's. Masangan Kulon Village, Sidoarjo Regency is one of the villages with a high wasting problem in toddlers. Education for toddler mothers is one of the activities that can provide benefits to increase knowledge so that it can change behavior and is expected to reduce nutritional problems in toddlers. Community service activities aim to increase the knowledge of mothers of toddlers about healthy, nutritious, balanced and dietary diversity for toddlers through education. The results of community service activities have increased knowledge before and after education. Increasing knowledge of toddler mothers is expected to be able to change behavior in feeding, especially in terms of dietary diversity.